Left External Iliac Vein Injury During Laparoscopic Pelvic Lymphadenectomy for Early-Stage Ovarian Cancer: Our Experience and Review of Literature - Tinelli, Raffaele; Dellino, Miriam; Nappi, Luigi; Sorrentino, Felice; D'Alterio, Maurizio Nicola; Angioni, Stefano; Bogani, Giorgio; Pisconti, Salvatore; Uccella, Stefano; Silvestris, Erica (Frontiers in Surgery, 2022)
Laparoscopic surgical staging is the standard treatment of early-stage ovarian tumors with similar survival outcomes if compared with laparotomic procedures. In this article, we report a case regarding an incidental external iliac vein injury during a pelvic lymphadenectomy for fertility sparing treatment of early-stage ovarian cancer with a video showing the laparoscopic repair without any consequence or side effect. A 36 year-old obese woman with Body Mass Index 30 kg/m2 referred at our hospital with an histological diagnosis of high grade ovarian serous carcinoma after a left laparoscopic salpingo-oophorectomy performed in another hospital. After an hysteroscopy with endometrial biopsy, a laparoscopic surgical staging with a pelvic and aortic lymphadenectomy with lymph-node dissection until the left renal vein, omentectomy, and appendectomy were performed. A thermal injury to the left external iliac vein occurred using the bipolar forceps during lymphadenectomy and was repaired after an immediate clamping of the site using endoclinch and the suction irrigator probe. The laceration on the iliac vein was successfully repaired using 10 mm laparoscopic titanium clips; after a follow-up of 42 months no recurrence was detected. In conclusion, laparoscopy is a safe and effective therapeutic option for fertility sparing treatment patients with early stage ovarian carcinoma with a significantly low morbidity and postoperative hospitalization, but it should be reserved for oncologic surgeons trained in advanced laparoscopic procedures and repair of vascular injuries potentially associated with high mortality rate.